Investigation of factors affecting the seam slippage of garments. Issue 21 (November 2019) - Chen, Daoling; Cheng, Pengpeng
Seam slippage often occurs with some garments during the process of wearing or washing, which not only affects the appearance of the garment but also influences garment quality. The purpose of this study is to find out the factors that affect the seam slippage of garments. In order to make the test results closer to those of the garment itself, this study first proposed to make the fabric into a Japanese woman's prototype sample, in order to simulate the garments produced by a garment enterprise. Then, according to standards GB/T 13772.2-2008/ISO 13936-2: 2004 and GB/T 21294-2014, samples were made and seam slippage at the armhole and side seam was tested. Experimental results reveal that the factors that cause the seam slippage of garments are the fabric, seam type and sewing thread. According to the regression analysis, the seam type has a significant effect on the seam slippage of the armhole and side seam, with Pearson correlation coefficients of −0.715 and −0.650, respectively. Thickness, weight, weft density and weave type of the fabric are also important in terms of seam slippage. The weight of the fabric is more significant than other factors; the significant values at the armhole and side seam are 0.009 and 0.002, respectively. In the linear equation, it is shown that weft breaking strength of the fabric only impacts the seam slippage at the side seam. Sewing thread is another important factor for the seam slippage of garments, and its influence on the armhole is obvious; the larger the sewing thread linear density of polyester material is, the smaller the seam slippage is.